Załączniki do ksiąg metrykalnych jako źródło historyczne do badań Subregionu Konińskiego w XIX wieku - Szewczyński, Piotr (Archiwa, Biblioteki i Muzea Kościelne, 2010)
The work presents the description of the documents-annexes to the register books connected with the documentation kept by the church offices of the Roman Catholic parishes from Russocice, Wyszyna, Turek, Koło, Brudzew and some others from this part of the diocese of Wrocław; and from the Evangelical-Augsburg parish in Władysławowo. The analysed documents are probably the remnants of the bigger collections which were damaged during the Second World War. These sources can be useful for further research on families, the etymology of names, social background, migration of the inhabitants of Eastern Great Poland. In the 19th century and at the beginning of the 20th century legislation on this issue said that a priest who was in charge of a parish was obliged to keep register office records. He was the person who was supposed to produce a marriage record before administering the sacrament of marriage. The four discovered sources which came under scrutiny in this article contain the documents of the people from a few nearby parishes who wanted to enter into matrimony. In the above mentioned sources there is information about social background of the couples, their birth and baptism dates, reading of the banns and marriage dates. In addition, these documents carry the municipal and church seals, and revenue stamps in Russian currency. This work also presents the fragments of the documents as sources for analyzing office practice and as encouragement to further research on family formation in this part of Eastern Great Poland.